The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jbm.a.37048
|View full text |Cite
|
Sign up to set email alerts
|

Carbon quantum dots‐embedded electrospun antimicrobial and fluorescent scaffold for reepithelialization in albino wistar rats

Abstract: A prosthetic scaffold development using fluorescent nanofiber is reported for an enhanced reepithelialization in wistar albino rats. In this study, a novel approach was followed to construct the biocompatible fluorescent nanofiber that will be helpful to monitor the tissue regeneration process. Here, a multifunctional carbon quantum dots (CQDs)‐embedded electrospun polyacrylonitrile (PAN) nanofiber was fabricated and characterized using standard laboratory techniques. The biodegradation ability was assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…55 Other studies (ISO 10993-5) have identified the cell viability in the range 80−120%, referring to the low toxicity on cells. 56,57 The cytotoxicity of the sample was compared with that of the untreated control with a cell viability of 100%. The cytotoxicity enhancement data have been intensively explored in determining the 50% cytotoxic concentration, or commonly called CC 50 , of each of the varied CDs (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…55 Other studies (ISO 10993-5) have identified the cell viability in the range 80−120%, referring to the low toxicity on cells. 56,57 The cytotoxicity of the sample was compared with that of the untreated control with a cell viability of 100%. The cytotoxicity enhancement data have been intensively explored in determining the 50% cytotoxic concentration, or commonly called CC 50 , of each of the varied CDs (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…180,181 In addition to the materials mentioned above, carbon-based materials also have the magnificent potential to result in electroactivity. These include graphite, 182,183 graphene, [184][185][186] graphene oxide, 187,188 reduced graphene oxide, [189][190][191] carbon nanofibers, 60,[192][193][194] carbon nanotubes, 156,195,196 fullerene, 197,198 carbon quantum dots, [199][200][201] and nanodiamonds. [202][203][204] Particular mechanical, electrical, thermal, and optical properties bring about the opportunity for carbon-based nanomaterials to be involved in the field of tissue repair.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…CDs can also be embedded inside patches for wound dressing purposes or inside nanofibrous materials commonly used in biomedical devices for a slow release and long-term antibacterial protection [ 150 , 151 ]. For instance, Jian et al [ 152 ] showed that spermidine/dopamin-based CDs (SPM/DA-CDs) can be used for the functionalization of 2-hydroxyethyl methacrylate, a polymer film that constitutes the main component of contact lenses.…”
Section: Cd-based Functional Materials For In Vivo Biomedical Applicationsmentioning
confidence: 99%